Sleep quality in team USA Olympic and Paralympic athletes - Anderson, T.; Galan-Lopez, N.; Taylor, L.; Post, E. G.; Finnoff, J. T.; Adams, W. M. (International Journal of Sports Physiology and Performance, 2024)
Adequate sleep is crucial for elite athletes` recovery, performance readiness, and immune response. Establishing reference ranges for elite athletes enables appropriate contextualization for designing and targeting sleep interventions.